The Potential and Future Perspectives of CRISPR-Cas 13 Technology in Cancer Therapy Application - Chen, Yuhe (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Cancer remains a significant global health challenge due to its genetic complexity and the diverse mutations, epigenetic modifications, and dysregulated signaling pathways involved. This complexity complicates effective treatment strategies. The CRISPR system, particularly CRISPR - Cas13, presents a promising therapeutic tool, offering precise RNA targeting with high accuracy and sensitivity. This paper examines the potential of Cas 13 in cancer therapy, focusing on four key areas: the mechanism of Cas13, Cas13  applications in cancer treatment, challenges and limitations. The results of the study showed that CRISPR-Cas13 can not only be used as a potential cancer diagnostic tool, but also regulate abnormal mRNA mutations and reduce cancer risk. By knocking down oncogenic lncRNA, CRISPR-Cas13 can inhibit the proliferation and migration of cancer cells. CRISPR-Cas13 has the potential to reduce cancer incidence and reduce cancer mortality through early diagnosis and intervention. In the future, technical optimization to address the off-target effects of Cas13 will be the key to its application in cancer treatment.